Crime in Warsaw in 1992 (Statistical Analysis) (Archives of Criminology, 1994)
This work contains a statistical analysis of crime in Warsaw in 1992 based on the data on crime recorded by the Warsaw Police Headquarters. Changes in the dynamics, structure, and spatial distribution of crime in the years 1988 to 1992 are shown in accordance with the city’s basic administrative division into 17 districts.Territorial differentiation of crime in areas subordinated to the separate police stations (47) is shown in figures and maps of rates and changes in crime in 1992 as compared to 1991. Separated because of their specific nature are typical big city areas, neighborhoods of railway stations and the airport, as well as suburbs.            Changes in crime recorded in Warsaw in 1989‒1992 were relatively much greater than those found on the national scale. An exception here was the year 1990 when a similar growth in the proportion of recorded offences took place both in Warsaw and Poland – by 64% and 61% respectively as compared 1989. After a rapid growth of recorded crime staring in 1989, a downward trend began in 1991 at a pace that was higher in Warsaw than all over Poland.            In 1992, the crime rate (mean numbers of offences recorded yearly per  100 thousand of the population of a given area) in Warsaw was 2.3 times higher than the national average which was a drop as compared to 1990 and 1991 when the indices were 2.7 and 2.6 respectively.            Changes in the extent of crime in the separate districts of Warsaw in 1989‒1992 have been depicted by chain indices of dynamics. The values of those indices manifest considerable differences in the changes in crime between the separate districts, and occurrence of opposing trends in succeeding years. The districts that had the greatest growth in crime in 1990 (Mokotów, Ochota, Praga Południe, Żoliborz) showed the greatest drop next year (1991). A similar trend could be found in 1992 in the districts of Praga Północ and Śródmieście (an increase, relatively high as compared to the other districts, followed by the greatest decrease). These findings may evidence both “displacement” of real crime, and the impact of other factors related to the activities of the police and public prosecutor’s office (in the spheres of both crime prevention and control, and the methods of recording offences).            As shown by analysis of the rates and structure of crime in the separate disricts of Warsaw, the different areas of the city are much differentiated in this repect. In 1991 and 1992, differentiation of the rates crime was three times higher as compared to 1990.            The highest crime rates could be found in Śródmieście – 10265.1, and Praga Północ – 6145.5; this resulted, among other things, from concentration of economic life and a high mobility of the population in those districts which stay busy for twenty-four hours a day. The lowest mean crime rates were found in Mokotów (3664).The next stage of statistical analysis of crime recorded by the police in Warsaw consists in the presentation of the territorial differentiation of crime in the areas of operation of the separate police stations. Differentiation of the crime  rates was very high, ranging from 1,700 offences per 100 thousand of the population recorded at the 3rd station to 27,559 recorded at the 17th station (in Śródmieście district). At the  same time, as was the case with crime analysed by city districts, a reverse trend of the changes in rates and intensity of crime could be found. In some areas which, admittedly, had the relatively lowest crime rates in 1992, there was a relatively high growth in crime as compared to 1991. In Śródmieście  district, despite the drop in crime in 1992 as compared to 1991 (which was the highest at the 17th station ‒ by 31% and the lowest at the 26th station – by 8%) the crime rates per 100 thousand of the population proved among the highest. This may confirm the thesis as to “displacement” of crime. On the  other hand, it may also result from different relations between the extent of real crime and that of recorded offences. What speaks for these latter conclusions are the results of regression and correlation analysis which manifest a significant correlation between the rates of recorded crime in general and offences against property: thefts of private property and breaking and entering of private buildings where the “dark numer” is high. Therefore, the distribution of crime in Warsaw is determined by offences against property where evaluation of the numer of  undetected offences is particularly difficult.As follows from the police data, the clearance rate of crime in Warsaw was differentiated according to both type and site of the offence. The highest mean clearance rate was found in Ochota district (27.5%), and the lowest in Praga Północ (16.3%). The probability of successful detection was highest with respect to traffic offences (0.93) and lowest in cases of breaking and entering (0.05). Clearance rate was highly differentiated (57%) in the case of car burglaries. The relatively highest probability of detection was found in Wola district (0.16), the lowest ‒ in Żoliborz (0.033) and Śródmieście  (0.038). The probability of detection of offences against persons in Warsaw in 1992 was about 0.6 (e.g. 60%), and against property – several per cent.The differentiation of both the dynamics and structure of crime in the separate districts of Warsaw and in areas of the separate police stations within the districts again confirms the thesis as to existence of areas that are particularly threatened with crime – the crime-generating areas. On the other hand, this differentiation suggests a large and indefinite numer of unrevealed or unrecorded offences.The present analysis, part of a study on the state of safety in Warsaw  initiated by the Superintendent of Warsaw Police and the Major of Warsaw,  confirmed the need for improving the data gathering system, securing the continuity of data, and the use of computer data carriers.